PERSEPSI MASYARAKAT JAWA DI KENCONG JEMBER TERHADAP WETON: STUDI BUDAYA ATAS DAMPAKNYA TERHADAP KEHARMONISAN RUMAH TANGGA - Gilang Haekal Ramadhan; Rizal Mumazziq Z (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This study aims to understand the perception of the Javanese community in Kencong Jember regarding weton and its impact on household harmony. A qualitative descriptive method was employed, involving in-depth interviews, participatory observation, and documentation. The main phenomenon revealed a strong belief in weton, particularly among traditional leaders and elders who view it as a determinant of partner compatibility and household harmony. However, the younger generation tends to see weton as a flexible cultural tradition rather than an absolute marriage determinant. Psychologically, belief in weton causes anxiety and conflicts, while communication and understanding serve as key factors for harmony among couples who marry despite incompatible wetons. The novelty of this study lies in revealing diverse perceptions and cultural adaptation (living tradition) amid social change and modernization within the Kencong Jember community context.